Negotovost kot merilo zanesljivosti meritev hrupa v okolju - Deželak, Ferdinand (Gradbeni vestnik, 2022)
Uncertainty as a measure of reliability has become established in all areas of metrology and quality monitoring. In Slovenia, it has been introduced in groundwater and air quality monitoring, but in the field of environmental noise it is still being enforced. A systematic literature review has shown that the estimation of uncertainty in measurements, modelling, analysis, estimation and reporting of environmental noise is necessary to achieve the accuracy of the final result and the reliability of measurements. Identifying all sources and contributors to uncertainty allows us to quantify the overall uncertainty, the direction of reduction and thus effective noise measures. This article aims to examine the role of measurement uncertainty in assessing the reliability of noise measurements in the built environment through a systematic review of regulatory requirements, recommendations and research findings. The article presents methods for identifying uncertainties with uncertainty budget. A case study examines the importance of uncertainty in improving the quality of environmental noise monitoring reports. The results are highly relevant as they emphasize the necessity and importance of the broader use of uncertainty in practice and thus raise the awareness of experts and researchers.
Keywords: environmental noise; hrup v okolju; measurement uncertainty; merilna negotovost; proračun negotovosti; reliability of measurements; uncertainty budget; zanesljivost meritev